1975
DOI: 10.1073/pnas.72.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma pigmentosum cells with normal levels of excision repair have a defect in DNA synthesis after UV-irradiation.

Abstract: Cells cultured from most patients suffering from the sunlight-sensitive hereditary disorder xeroderma pigmentosum are defective in the ability to excise ultraviolet light (UV)-induced pyrimidine dimers from their DNA. There is, however,-one class of these patients whose cells are completely normal in this excision repair process. We have found that these cells have an abnormality in the manner in which DNA is synthesized after UVirradiation. The time taken to convert initially lowmolecular-weight DNA synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
241
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(261 citation statements)
references
References 33 publications
(42 reference statements)
20
241
0
Order By: Relevance
“…Additionally I and others had shown that caffeine inhibited PRR in rodent cells [21]. Remarkably, we found that it had no effect on PRR in normal human fibroblasts, but completely inhibited the already deficient PRR in XPV fibroblasts, thus generating a huge difference between the normal and XPV cells [22]. In 1970s, effects of caffeine were interpreted in terms of its inhibitory effects on cyclic AMP phosphodiesterase, whereas these days everybody thinks of it as an inhibitor of ATR and ATM.…”
Section: Xp Variants Cockayne Syndrome and Other Repair-deficient DImentioning
confidence: 62%
See 1 more Smart Citation
“…Additionally I and others had shown that caffeine inhibited PRR in rodent cells [21]. Remarkably, we found that it had no effect on PRR in normal human fibroblasts, but completely inhibited the already deficient PRR in XPV fibroblasts, thus generating a huge difference between the normal and XPV cells [22]. In 1970s, effects of caffeine were interpreted in terms of its inhibitory effects on cyclic AMP phosphodiesterase, whereas these days everybody thinks of it as an inhibitor of ATR and ATM.…”
Section: Xp Variants Cockayne Syndrome and Other Repair-deficient DImentioning
confidence: 62%
“…The data from that blind experiment are shown in Fig. 4 of the paper that was published in PNAS in 1975 (see Fig 2B) [22] and is my most cited paper. We then built on this work and spent a lot of time in the next few years debating in the literature and at meetings whether the replication fork was blocked at lesions, whether it restarted beyond the lesion after a delay, or whether synthesis bypassed the lesion directly without discontinuities (e.g.…”
Section: Xp Variants Cockayne Syndrome and Other Repair-deficient DImentioning
confidence: 99%
“…In XP-V cells that lack the translesional DNA Pol η, UV damage to DNA causes an asymmetric replication fork arrest due to a replication block on the leading strand of DNA [41][42][43][44][45][46]. These structures trigger the activation of intra-S-phase checkpoints [44].…”
Section: Discussionmentioning
confidence: 99%
“…Most XP patients are deficient in the ability to remove UV photoproducts from their DNA by nucleotide excision repair (NER), but about 20 % are normal in this respect and have problems in replicating their DNA after UV-irradiation [5]. The gene defective in these XP variants encodes polη.…”
Section: Tls Polymerasesmentioning
confidence: 99%